2019
DOI: 10.1371/journal.pone.0210850
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptomics and proteomics forecast analysis for potential genes regulating the Columbian plumage color in chickens

Abstract: BackgroundColoration is one of the most recognizable characteristics in chickens, and clarifying the coloration mechanisms will help us understand feather color formation. “Yufen I” is a commercial egg-laying chicken breed in China that was developed by a three-line cross using lines H, N and D. Columbian plumage is a typical feather character of the “Yufen I” H line. To elucidate the molecular mechanism underlying the pigmentation of Columbian plumage, this study utilizes high-throughput sequencing technology… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 76 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…The study revealed co-differential expression of 170 genes/proteins, with 122 genes/proteins displaying the same expression trends in both transcriptome and proteome profiles. The low to moderate correlation could be attributed to a variety of factors, including translation efficiency, alternative splicing, mRNA stability, folding, assembly, transport and localization, secretion, and degradation (48)(49)(50). Since the present study utilized publicly available transcriptomics databases and proteomics results from the current assessment, this 122 codifferentially expressed genes/proteins might be considered as representative of altered biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed co-differential expression of 170 genes/proteins, with 122 genes/proteins displaying the same expression trends in both transcriptome and proteome profiles. The low to moderate correlation could be attributed to a variety of factors, including translation efficiency, alternative splicing, mRNA stability, folding, assembly, transport and localization, secretion, and degradation (48)(49)(50). Since the present study utilized publicly available transcriptomics databases and proteomics results from the current assessment, this 122 codifferentially expressed genes/proteins might be considered as representative of altered biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The matching line of the “Yufen 1” layer was authorized by the National Commission on Livestock and Poultry Genetic Resource in 2015. A closed breeding method was used to develop line H by crossing barred plumaged-original Gushi chicken (GS) with an egg-laying brown-shelled Babcock B-380 grandparent line C. As the progenitor, line H is characterized by early sexual maturity, a fast plumage line, a high egg production, and a Columbian feather pattern [ 12 ]. However, knowledge on the genomic structure of the “Yufen 1” H line chicken (YF) is still scant.…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt signaling pathway plays a vital role via the microphthalmia-associated transcription factor ( Mitf ) in the development of melanophores ( Jin et al, 2001 ). Wnt7b is a direct target of canonical BMP signaling in hair follicle stem cells, and wnt7b expression reaches a peak during the development of black and white striped feather hair follicles in the neck of eight-week-old chicken ( Kandyba and Kobielak, 2014 ; Wang et al, 2019 ). In Ctenophorus decresii , wnt7b showed stronger expression in skin with a high melanin concentration ( Mclean et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%